DESULFURIZATION OF STEEL USING INJECTOR UNIT “VELCO” - V. V. Pivtsajev; V. I. Djachenko; E. A. Proskurin (Литьë и металлургия)
The full technology of application of powder-like materials with injecting of them through unit «Velco» at out-of-furnace processing of steel is described.